Monocular Clinical Outcomes and Range of Near Vision following Cataract Surgery with Implantation of an Extended Depth of Focus Intraocular Lens - Rahul T. Pandit (Journal of Ophthalmology)
Importance. A full range of near and intermediate vision has not been clinically evaluated for the Symfony extended depth of focus intraocular lens (EDOF IOL). Background. To evaluate the monocular range of near visual acuity with an EDOF IOL. Design. Retrospective case series. Participants. Consecutive patients of a single surgeon from January 2017 through March 2018. Methods. Phacoemulsification with implantation of an EDOF IOL. Main Outcome Measures. Uncorrected distance visual acuity (UDVA), uncorrected near visual acuity (UNVA), corrected distance visual acuity (CDVA), distance-corrected near visual acuity (DCNVA), range of DCNVA, and optimal near focal length. Results. Seventy-six eyes of 48 patients (34 or 71% female, mean age: 68 years) were included with a mean follow-up of 68 days. Mean values were as follows: logarithm of the minimum angle of resolution (logMAR) UDVA 0.02 ± 0.09, logMAR UNVA 0.12 ± 0.09 at a mean distance of 51 cm, logMAR CDVA −0.05 ± 0.07, logMAR DCNVA 0.08 ± 0.07 at a mean distance of 51 cm, and a spherical equivalent of −0.16 diopters ±0.35. Percentage of eyes achieving DCNVA of 20/30 were 84% at 36 cm, 92% at 41 cm, 99% at 51 cm, 93% at 61 cm, and 74% at 71 cm. DCNVA of 20/40 or better was achieved in nearly 100% of eyes over a range of 35 cm. Conclusions and Relevance. The Symfony EDOF IOL achieved excellent distance visual acuity while providing a 35 cm range of near visual acuity at levels useful for many tasks in nearly all patients.